Is the internet a sufficient source of information on sarcoidosis? - Buschulte, Katharina; Höger, Philipp; Ganter, Claudia; Wijsenbeek, Marlies; Kahn, Nicolas; Kriegsmann, Katharina; Wilkens, Finn M.; Fisher, Jolene H.; Ryerson, Christopher J.; Herth, Felix J. F.; Kreuter, Michael (Frontiers in Medicine, 2023)
Introduction – Many patients use the internet as a source of health information. Sarcoidosis is a complex disease and internet resources have not yet been analysed for reliability and content. Aims – The aim of our study was to investigate the content and the quality of information on sarcoidosis provided by internet resources. Methods – Google, Yahoo and Bing were searched for the term “sarcoidosis” and the first 200 hits were saved in each case. Those websites that met the inclusion criteria (English language, no registration fees, relevant to sarcoidosis) were then analysed by two independent investigators for readability, quality (HON, JAMA, DISCERN), and content (25 predefined key facts) of the provided information. Results – The websites were most commonly scientific or governmental (n= 57, 46%), and median time since last update was 24 months. Quality was rated with a median JAMA score of 2 (1; 4) and a median overall DISCERN score of 2.4 (1.1; 4.1), both scores represent partially sufficient information. 15% of websites had a HON certificate. Website content measured by median key fact score was 19 (range 2.5-25) with lowest scores for acute versus chronic course of disease, screening for extrapulmonary disease, and diffuse body pain. Worse results were achieved in industry websites and blogs (p= 0.047) with significant differences regarding definition (p= 0.004) and evaluation (p= 0.021). Discussion – Sarcoidosis related content of internet resources are partially sufficient; however, several important aspects are frequently not addressed and quality of information is moderate. Future directions should focus on providing reliable and comprehensive information on sarcoidosis; physicians from different disciplines and patients including self-support groups should collaborate on this.